Management of Lumbar Disc Herniation with Radiculopathy Through Ayurveda - A Case Study - Lekshmipriya,; P. Benedict,; M.S Deepa, (International Journal of Ayurveda and Pharma Research, 2022)
Lumbar disc herniation is a major health problem, affecting the most productive population globally. It has closest resemblance with Gridhrasi mentioned in Ayurvedic classics. Treatments available in conventional sciences have limitations such as relapse of acute episodes. Here an effort was made to treat a case of L5-S1 disc extrusion with radiculopathy using a comprehensive Ayurveda treatment protocol. The protocol includes a set of treatment procedures along with certain internal medicines. Changes were analysed with the help of VAS scale, SLRT and Oswestry disability index and showed significant improvements. This case is an evidence to demonstrate the effectiveness of Ayurveda treatments in case of LDH with radiculopathy.